2017
DOI: 10.1080/13561820.2017.1366895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of team composition on student perceptions of interprofessional teamwork: A 6-year cohort study

Abstract: Interprofessional education (IPE) provides students with opportunities to learn about the roles and responsibilities of other professions and develop communication and teamwork skills. As different health professions have recognised the importance of IPE, the number of disciplines participating in IPE events is increasing. Consequently, it is important to examine the effect group structure has on the learning environment and student knowledge acquisition during IPE events. The purpose of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
7
0
6
Order By: Relevance
“…These findings parallel results from relatively short (<6 hours) interactive interprofessional educational seminar experiences, which demonstrated positive changes in attitudes towards interprofessional learning and collaboration among undergraduate and graduate health professions students (Dahlgren et al, 2018;Gould et al, 2017;Mishoe et al, 2018;Wellmon et al, 2012). Previous research has demonstrated improvement in overall attitudes towards interprofessional education and collaborative practice is possible after IPE focused coursework and our findings highlight similar results with a shorter intervention (Hood et al, 2014;Lairamore et al, 2018;Ruebling et al, 2014). A focus on roles and responsibilities of the professions within the interprofessional team for shorter interprofessional education experiences can provide important avenues for improving understanding and sharing of expertise amongst health professions students (Gould et al, 2017).…”
Section: Attitudes Towards Teamworksupporting
confidence: 83%
“…These findings parallel results from relatively short (<6 hours) interactive interprofessional educational seminar experiences, which demonstrated positive changes in attitudes towards interprofessional learning and collaboration among undergraduate and graduate health professions students (Dahlgren et al, 2018;Gould et al, 2017;Mishoe et al, 2018;Wellmon et al, 2012). Previous research has demonstrated improvement in overall attitudes towards interprofessional education and collaborative practice is possible after IPE focused coursework and our findings highlight similar results with a shorter intervention (Hood et al, 2014;Lairamore et al, 2018;Ruebling et al, 2014). A focus on roles and responsibilities of the professions within the interprofessional team for shorter interprofessional education experiences can provide important avenues for improving understanding and sharing of expertise amongst health professions students (Gould et al, 2017).…”
Section: Attitudes Towards Teamworksupporting
confidence: 83%
“…In policy documents, IPE research, guidelines, reports and textbooks, the concept of teamwork is linked to interprofessional collaboration in health care (CAIPE, 2017;Fox et al, 2018;Frenk et al, 2010;IPEC, 2011;Lairamore et al, 2018;NM of Health and Care Services, 2015;NM of Education, 2012;Reeves, Lewin, Espin & Zwarenstein, 2010b, Reeves et al, 2017WHO, 2010). A team is understood as a group of people pursuing a common goal together (CAIPE, 2017) and teamwork as when the people in the group relate themselves to the group, clarify roles, tasks and goals, create interdependence, integrate with each other and take on responsibility for the performance of the group (Reeves et al, 2010b).…”
Section: Introductionmentioning
confidence: 99%
“…20 Study results support IASP recommendations for small group work 22 and align with research demonstrating improved social interaction, learning scores, and student satisfaction in smaller groups. 1 , 26 It is plausible that psychological safety conferred by small groups (ie, students feel comfortable asking questions) may contribute to knowledge exchange. 46 Regardless of the session size and delivery mode, however, students in this study indicated that opportunities for interaction enhanced their engagement in learning.…”
Section: Discussionmentioning
confidence: 99%